Nonlinear absorption properties of 5,10-A2B2 porphyrins - correlation of molecular structure with the nonlinear responses - BLAU, WERNER; SENGE, MATHIAS; WANG, JING (My University, 2013)
The nonlinear absorption properties of two series of novel free base and metalated meso 5,10-A 2 B 2 sub- stituted porphyrins, both bearing p -tolyl as an A substituent and TMS-ethynyl or bromine as a B substitu- ent, were investigated with the open Z-scan technique at 532 nm in the ns time regime. Most of the compounds exhibited a transmission drop with increasing input fl uence. This behavior is desirable for their applications in optical limiting. More complex responses: a drop in transmission followed by an increase in transmission or an increase in transmission followed by a transmission drop, with increasing input fl uence, were detected for certain compounds. All of the recorded responses were successfully fi tted with a four-level model with simultaneous two-photon absorption arising from the higher excited states (consecutive one- + one- + two-photon absorption). The TMS-ethynyl group was found to be a more e ffi cient meso substituent in optical limiting than the bromine atom. Indium, lead and zinc com- plexes with TMS-ethynyl substituents were the strongest positive nonlinear absorbers amongst com- pounds studied which makes them the most interesting candidates for optical limiting application.
PUBLISHED
Keywords: positive nonlinear absorbers; positive nonlinear absorbers; Nanoscience & Materials